Patterns of waterbird diversity in central western Madagascar: where are the priority sites for conservation? - Young, H. Glyn; Young, R. P.; Razafindrajao, F.; Bin Aboudou, Abdallah Iahia; Fa, J. E. (Wildfowl, 2014)
Madagascar still retains extensive wetlands important for fishing, hunting and agriculture. They also support a high proportion of the island’s globally threatened endemic birds. However, as a result of widespread modification through human activity, wetlands are under severe pressure across the island, resulting in the decline of many waterbird species. For the effective conservation of waterbirds in Madagascar, it is vital that wetlands supporting important assemblages of species are identified and protected. In this study, we surveyed the wetlands of central western Madagascar (southern Melaky and Menabe Regions) to investigate patterns of waterbird diversity and map priority sites. Thirty-four wetland sites were surveyed in 2004, during which a total of 56 waterbird species were recorded. Waterbird species richness was associated with the size of the water body and presence of rice cultivation. All sites were ranked according to an index of vulnerability, based on the cumulative score of the degree of threat for every wetland bird species found in a site. We show that wetlands in western Madagascar hold important numbers of several globally threatened species; five of the rarest bird species in Madagascar are found here. The 10 highest-ranking wetland sites fall within BirdLife International IBAs, but four wetlands fall outside current or planned protected areas. We recommend that monitoring of wetland sites in western Madagascar is undertaken at regular intervals and that all sites are included in a network of protection that can ensure the survival of wetland bird diversity in the country.